The Effect Of Biocides Addition Against Morphology And Size Distribution Of Bacteria Cells In Injection Water - Zulkifliani Zulkifliani; Junita Trivianty Musu (Scientific Contributions Oil and Gas, 2011)
Produced water is the water produced along with oil and gas. Produced water contains small to large quantities of suspended solids, such as corrosion material, scale, clay, wax, oil residues, and also bacteria and their metabolites. Produced water which is re-injected into the reservoir without having proper water treatment can lead to rock plugging and reservoir damage. One of the causes of reservoir damage is the occurrence of bacteria cells and their metabolites. Biocides are used to reduce the viability of bacteria cells in produced water to be applied as water injection. The aim of this study is to understand the effect of biocides on morphology and the size distribution of bacteria cells in injected water. Observations with scanning electron microscope (SEM) and laboratory tests showed that provision of biocides can cause damage of cytoplasmic membrane on bacteria cells or cells lyses and significantly reduced size distribution of bacteria cells.